Correlation between Stock and Bond market in UK - Shuja, Rohama (2020)
The scope of the study was aimed to give investors a glimpse of correlation between the stock market and the bond market. This study has an important implication for the portfolio managers and that is the relationship studied between the bond market volatility and the stock market volatility. This relationship is crucial in asset allocation decisions.